Irregularity and time-series trend analysis of rainfall Baybay City, Leyte, Philippines - May Anne Aclan; Ma. Grace Curay (Annals of Tropical Research, 2025)
This study examined rainfall trends and variability in Baybay City, Leyte, Philippines, from 1991 to 2020. Utilizing the Mann–Kendall test, Sen's slope method, and Coefficient of Variation (CV), the analysis reveals a 26.41% increase in mean annual rainfall compared to earlier decades. However, annual and seasonal trends lack statistical significance, suggesting random fluctuations. Seasonal variability is highest during MAM (March, April, May), with CV of 59.76% followed by DJF (December, January, February), with a CV of 40.72%. These fluctuations are influenced by transitional monsoons and the intertropical convergence zone (ITCZ). Despite Baybay City's Type IV climate with year-round rainfall distribution, fluctuations reflect natural variability and extreme weather events. The findings emphasize the need for adaptive measures in water resource management, agriculture, and infrastructure to address climate variability and ensure community resilience.